Kuhn, Fleck and Archaeological Evidence: An Omnivorous Strategy to Study the History of Archaeology - Milosavljević, Monika (Ex Novo: Journal of Archaeology, 2024)
The majority of the current histories on the social facets of scientific work rely theoretically on Kuhn’s The Structure of Scientific Revolutions, whose ‘paradigm’ has since become limited due to a rethinking of the epistemology of knowledge creation. Accordingly, Ludwik Fleck, whose notions allow for better micro-historiographies to surface as a supplement to the paradigm, have come to the fore with their applicability stemming from his The Genesis and Development of Scientific Fact. A hybrid omnivore strategy between them may be further supplemented by the contemporary philosophy of science of evidential reasoning in archaeology. Applying this theoretical background, specific attention in this paper is paid to the archaeology of the former Yugoslavia, in which a monumental shift occurred. Prior to World War II, it consisted of lone individuals; however, with the introduction of a culture-historical approach, considerable growth occurred in archaeology after World War II, emerging as an emancipatory force in the service of ideology. Through an omnivore perspective, an examination of the archaeology of the former Yugoslavia presents a broader picture of the mechanisms of scientific development.